Genome-wide analysis of IQ67 domain (IQD) gene families in Brachypodium distachyon - (:unkn) unknown (SOUTHERN CROSS PUBL, 2013)
In plants, Ca2+ concentration is important for the regulation of developmental processes and responses against biotic and abiotic stress factors. The eukaryotic Ca2+ binding protein calmodulin (CaM: CALcium MODULating protelN) was found in Arabidopsis which contains a characteristic plant-specific IQ67 (Ile, Glu) domain (IQD). In this study, a genome wide analysis was performed in Bracyhpodium distachyon to identify IQD genes. Using several bioinformatics tools, we determined 23 BdIQD genes which were distributed on all chromosomes and the highest gene number was detected on chromosome 2 including 12 IQD genes. 22 of the predicted proteins were considered to be basic proteins. Gene duplication analysis revealed that 8 of 23 BdIQD genes were involved in duplication event, either segmental or tandem. Phylogenetic analysis showed that two main groups were observed in joined tree with rice and Arabidopsis. Especially, monocot species (Brachypodium and rice) were grouped together with the highest bootstrap value (100%), whereas monocot and dicot species (Arabidopsis) were clustered with lower bootstrap values. Digital expression profile analysis indicated that the most of the BdIQD genes were expressed in leaves (8 genes) and flowers (6 genes), respectively. In conclusion, this comparative genomics analysis contributes to understanding IQD genes in grass species.
Keywords: IQD genes; IQ67 domain; calmodulin (CAM); Brachypodium; genome wide analysis; MORPHOLOGICAL VARIATION; ARABIDOPSIS-THALIANA; CA2+ SIGNALS; CALCIUM; PROTEIN; GRASS